Chemical composition, pharmacology and pharmacokinetic studies of GuHong injection in the treatment of ischemic stroke - Wang, Qiuyue; Yang, Zhihua; Guo, Liuli; Li, Zhenzhen; Liu, Yangxi; Feng, Shaoling; Wang, Yanxia (Frontiers in Pharmacology, 2023)
GuHong injection, is composed of safflower and N-acetyl-L-glutamine. It is widely used in clinical for cerebrovascular diseases, such as ischemic stroke and related symptomsdiseases. The objective of this review is to comprehensively summarizeexamine the most recent information related to GuHong in the treatment of stroke, including chemical composition, clinical studies, potential pharmacological mechanisms and pharmacokinetics, . Additionally, it examines possible scientific gaps in current study and aims to provide a reliable reference for future GuHong studies.discuss possible scientific gaps, and provide a reliable reference for future studies. The systematic review revealsed that the chemical composition of safflower in GuHong wasis more than 300 chemical components in five categories. GuHong injection is primarily used in clinical applications for acute ischemic stroke and related diseases. Pharmacological investigations have indicated that GuHong acts in the early and recovery stages of ischemic stroke by anti-inflammatory, anti-oxidative stress, anti-coagulation, neuroprotective and anti-apoptotic mechanisms simultaneously. Pharmacokinetic studies found that the main exposed substances in rat plasma after GuHong administration wereare hydroxysafflor yellow A and N-acetyl-L-glutamine, and that N-acetyl-L-glutamine GuHong injection for ischemic stroke could exert its pharmacological effect across the blood-brain barrier. As a combination of Chinese herbal and Chemical chemical drug, GuHong injection has great value in drug research and clinical treatment, especially for ischemic stroke disease. This article first provides a comprehensive and systematic review of GuHong. This article represents a comprehensive and systematic review of existing studies on GuHong injection, including chemical composition, pharmacological mechanism, and pharmacokinetics, which provides reference significance for the clinical treatment of ischemic stroke with GuHong, as well as provides guidance for further study.